Analisis Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Sumber Alfaria Trijaya Tbk (Alfamart) - Deviana Deviana; Realize Realize; Ronald Wangdra (LPPM Universitas Putera Batam, 2022)
The purpose of this research is to determine 1. Effect of Work Discipline on Employee Performance in PT Sumber Alfaria Trijaya TBK (Alfamart) partially; 2. Effect of Work Motivation on Employee Performance partially; and (3) Effect of Work Discipline and Motivation on Employee Performance Work simultaneously. Methods: Total population in this study was 138 employees and the amount of sample in this study was 138 employees, Data Collection Techniques by questionnaire, sampling technique research using sampling techniques saturated. Analysis method is Quantitative Analysis, Quantitative Analysis with Multiple Linear Regression, determination (R Square), to determine the factors that influence employee performance with the coefficient of determination in Partial (r2) and simultaneous (R2). To test the hypothesis with the t-Test (Partial) and F-Test (Simultaneously), with a significance level (α = 0.05). The results showed that the influence of the variable Work Discipline Employee Performance is equal to 0.537 (53.70%). Work Motivation variable amount of influence on employee performance is equal to 0.887 (88.70%). The magnitude of the effect of variable Work Discipline and Motivation on Employee Performance Working simultaneously on PT Sumber Alfaria Trijaya TBK (Alfamart) amounted to 4,065 (40.65%).